Molecular Analysis of Cluster Headache. Issue 1 (January 2015) - Zarrilli, Federica; Tomaiuolo, Rossella; Ceglia, Carlo; Lombardo, Barbara; Izzo, Barbara; Castaldo, Giuseppe; Pastore, Lucio; De Simone, Roberto
<x xml:space="preserve">Abstract</x> Objectives: Cluster headache (CH) is characterized by severe, recurrent, unilateral attacks of extreme intensity and brief duration. Variants in a myriad of genes were studied in sporadic CH patients, often with conflicting results. Methods: We studied gene mutations in some candidate genes, hypocretin receptor 2, Clock, and alcohol dehydrogenase 4 (ADH4), in 54 unrelated sporadic CH patients and in 200 controls in 8 kindreds/families that included more affected and nonaffected cases. Furthermore, we performed the whole-genome scanning by comparative genomic hybridization, searching for rearrangements associated with DNA gain or loss in a subset of sporadic and familial CH and control participants. Results: The analysis of candidate genes revealed that only allele and genotype frequency of the 2 ADH4 mutations resulted significantly between sporadic CH and controls; the same mutations were homozygous in CH patients from 2 families. The comparative genomic hybridization analysis revealed 2 novel rearrangements that involved the intron regions of thyrotropin-releasing hormone-degrading enzyme and neurexin 3 (NRXN3) genes, respectively. The first arrangement was present either in CH or in controls, whereas the second one was specifically found in some sporadic and familial CH cases. Conclusions: Our data (although obtained on a small number of cases) confirm the genetic heterogeneity of CH, suggesting that mutations in the ADH4 gene and a novel rearrangement involving NRXN3 gene might be related to CH in a subset of cases.